2014
DOI: 10.1159/000358881
|View full text |Cite
|
Sign up to set email alerts
|

Enrofloxacin Enhances the Formation of Neutrophil Extracellular Traps in Bovine Granulocytes

Abstract: Several antibiotics are known for their ability to accumulate in neutrophils and thereby modulate the antimicrobial functions of those cells. This study demonstrates for the first time that an antibiotic, namely the fluoroquinolone enrofloxacin, enhances the formation of bovine neutrophil extracellular traps (NETs). Pharmacologically inactivated NADPH oxidase or peptidyl-arginine deiminase-4 distinctly reduced enrofloxacin-induced NET formation. Additionally, when cells were treated with cytochalasin D or noco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Other studies have also reported that cytoskeletal inhibitors had no effect on NET formation in response to Paracoccidioides brasiliensis or gold nanoparticles [49,50]. Neeli et al [51] reported that a 10 μM treatment with either the microtubule inhibitor nocodazole or cytochalasin D diminished histone deamination and NET release in response to LPS, and similar results were documented by Jerjomiceva et al [52] using enrofloxacin-treated bovine neutrophils. The basis for the divergent results of these studies is not clear, but more research is needed to better define the role of the cytoskeleton during the processes of ETosis in neutrophils and macrophages.…”
Section: Cellular Pathways Implicated In Met Releasesupporting
confidence: 55%
“…Other studies have also reported that cytoskeletal inhibitors had no effect on NET formation in response to Paracoccidioides brasiliensis or gold nanoparticles [49,50]. Neeli et al [51] reported that a 10 μM treatment with either the microtubule inhibitor nocodazole or cytochalasin D diminished histone deamination and NET release in response to LPS, and similar results were documented by Jerjomiceva et al [52] using enrofloxacin-treated bovine neutrophils. The basis for the divergent results of these studies is not clear, but more research is needed to better define the role of the cytoskeleton during the processes of ETosis in neutrophils and macrophages.…”
Section: Cellular Pathways Implicated In Met Releasesupporting
confidence: 55%
“…Interestingly, a similar EV-mediated export of deiminated histones, as observed in cow serum-EVs in the current study, was recently identified in the naked mole-rat, an animal with unusual immunological and metabolic traits [98], as well as in alligator, also an animal with unusual antimicrobial, including anti-viral responses [93]. Deiminated histone H3 is commonly used as an indicator for neutrophil extracellular trap formation (NETosis) [31,244], which has been related to PAD4 and implicated in anti-viral responses in cattle respiratory syncytial virus disease [42], in response to parasitic infections in cattle [245][246][247] as well as in response to certain antibiotics [248]. Interestingly, in crocodilians, extracellular histones H2A and H4 have been identified to act as inhibitors of viral (HIV) infection in vitro [249], although roles for post-translational deimination were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mechanistical studies to identify molecular insights in the pathways involved in bovine ET formation have been performed. Treatment of bovine neutrophils with fluoroquinolone enrofloxacin led to increased protein expression of PAD4 and enhanced levels of citH3 and NET formation [56]. An inhibition of actin and tubulin filaments in bovine neutrophils led to reduced formation of NETs [56], which has also been described for human neutrophils by Neeli and colleagues [125].…”
Section: Bovinaementioning
confidence: 56%